Biological Guided Carbon-Ion Microporous Radiation to Tumor Hypoxia Area Triggers Robust Abscopal Effects as Open Field Radiation - Huang, Qingting; Sun, Yun; Wang, Weiwei; Lin, Lien-Chun; Huang, Yangle; Yang, Jing; Wu, Xiaodong; Kong, Lin; Lu, Jiade Jay (Frontiers in Oncology, 2020)
Recently, a growing number of studies focus on partial tumor irradiation to induce the stronger non-target effects. However, the value of partial volume carbon ion radiotherapy (CIRT) targeting hypoxic region of a tumor under imaging guidance as well as its effect of inducing radiation induced abscopal effects (RIAEs) have not been well investigated. Herein, we developed a technique of Carbon Ion Microporous Radiation (CI-MPR), guided by 18F-FMISO PET/CT, for partial volume radiation targeting the hypoxia area of a tumor and investigated its capability of inducing abscopal effects. Tumor-bearing mice were inoculated subcutaneously with breast cancer 4T1 cells into the flanks of both hind legs of mouse. Mice were assigned to three groups: Group I: control group with no treatment; Group II: carbon ion open field radiation (CI-OFR group) targeting the entire tumor; Group III: partial volume carbon ion microporous radiation (CI-MPR group) targeting the hypoxia region. The tumors on the left hind legs of mice were irradiated with single fraction of 20 Gy of CIRT. Mice treated with CI-MPR or CI-OFR showed that significant growth delay on both the irradiated and unirradiated of tumor as compared to the control groups. Tumor regression of left tumor irradiated with CI-OFR was more prominent as compared to the tumor treated with CI-MPR, while the regression of the unirradiated tumor in both CI-MPR and CI-OFR group was similar. Biological-guided CIRT using the newly developed microporous technique targeting tumor hypoxia region could induce robust abscopal effects similar to CIRT covering the entire tumor.